780 POTENTIAL RELATIONSHIP BETWEEN MITOCHONDRIAL FERRITIN EXPRESSION AND CARDIOTOXICITY IN PATIENTS UNDERGOING ANTHRACYLINE CHEMOTHERAPY. (15th December 2022) - Marchionni, Giulia; Levi, Sonia; Pontara, Andrea; Santambrogio, Paolo; Prat, Valentina Da; Bucchi, Annalisa; Maria Ferreri, Andrés José; Zambetti, Milva; Foppoli, Marco; Gianni, Luca; Ciceri, Fabio; Margonato, Alberto; et al.
Abstract: Background: Anthracyclines effectiveness is burdened by numerous side effects, among which cardiotoxicity (CTX) is the one carrying the highest impact on survival. Prevention of CTX is known to be far more effective than its treatment. Nonetheless, present patients stratification does not predict different post-treatment outcomes. The inter-individual variability in the response to treatment likely resides at the molecular level. In this context, mitochondrial ferritin (FtMt) has been studied in preclinical models of doxorubicin-induced cardiotoxicity. Both in cell lines and animal models, overexpression of this protein has been found to be protective against the cytotoxic oxidative damage deriving from anthracycline use. Aim of the study: The primary aim of the study was to evaluate – for the first time in humans and in mouse myocardial cells lines – the expression of FtMt and its relationship with the potential development of cardiotoxicity in patients undergoing chemotherapy with anthracyclines. Methods: Twenty-nine patients referred to our Oncology Outpatient Clinic to start treatment with anthracyclines – for either lymphoma or breast cancer – were enrolled before treatment initiation. All patients were above 18 years of age and free from any cardiovascular pathology at baseline. Troponin T (TnT), Brain Natriuretic Peptide (NT-proBNP), FtMt and creatinine were evaluated at baseline, before any chemotherapy cycle, at the end of the protocol, at 6 and 12 months from the first cycle. TnT and NT-proBNP were quantified through ECLIA and the expression of FtMt through qRT-PCR performed on peripheral white blood cells. Left ventricular function was evaluated through standard echocardiography at baseline, at the end of chemotherapy, at 6 and 12 months. Furthermore, variations in FtMt expression in response to doxorubicin treatment were studied on mouse primary cardiomyocytes. Results: Direct evaluation of FtMt expression in mouse myocardial cells showed higher levels of FtMt in cardiomyocytes exposed to doxorubicin (p=0.0239). In the clinical model FtMt expression was found to be decreased after treatment initiation, with a trend that in the descriptive analysis appeared to be opposite to the one registered for TnT. For any unit of FtMt at baseline, single TnT values after treatment and at one year were found to be decreased of 1, 89 ng/L and of 1, 57 ng/L, respectively. TnT was the only cardiac parameter showing significant variation following anthracycline administration, with an average increase of 10 ng/L (p<0, 0001) and 15, 8 ng/L (p=0, 0071) in breast cancer and lymphoma patients respectively and remained elevated at follow-up only in the lymphoma group with a difference of 11, 35ng/L at 1 year (p=0, 0017). No occurrence of CTX – defined according to international guidelines - was found in the population under study. Conclusions: Our results confirm that exposure to anthracyclines influences FtMt expression. The study performed on mouse primary cardiomyocytes demonstrate for the first time the ability of cardiac myocytes to increase FtMt expression in response to doxorubicin. In the clinical model any additional unit of FtMt at baseline was associated with a reduction in TnT values at the end of the treatment and at 1 year, potentially indicating a protective role of this protein in this context. The lack of frank cardiotoxicity in this group impeded the evaluation of the prognostic meaning of this event. In the future drugs able to upregulate the expression of this protein should be investigated as potential strategy to prevent anthracycline-induced cardiotoxicity.